Distinct DNA Metabolism and Anti-proliferative Effects of Goat Urine Metabolites: An Explanation for Xeno-tumor Heterogeneity - Kumar, Ajay; Swami, Swati; Sharma, Nilesh K. (Current Chemical Biology, 2020)
Background: The tumor microenvironment, including microbiome populations in the local niche of several types of solid tumors like mammary and colorectal cancer are distinct. The occurrence of one type of cancer over another varies from animals to human individuals. Further, clinical data suggest that specific cancer types such as mammary and colorectal cancer are rare in ruminants like goat. Methods: Fresh urine samples were collected from healthy ruminants (cow, goat, buffalo, ox), non-ruminant animals (horse, jenny) and human. Further, these urine samples were subjected to fractionation by drying, vortexing, centrifugation and sterile filtration in DMSO extraction solvent. Collected urine DMSO fraction (UDF) samples from all sources were subjected to DNA metabolizing assay with plasmid DNA pBR322 and genomic DNA of MCF-7 cells. Next, based on the discernible DNA metabolizing effects of goat UDF among other sources, goat UDF was tested for anti-proliferative effects upon HCT-116 and MCF-7 cells using Trypan blue dye exclusion assay. Results: This paper reports that goat UDF possesses very clear DNA metabolizing effects (up to 95%) upon plasmid and genomic DNA compared to other ruminants, non-ruminants and human UDF samples. Interestingly, autoclaving of goat UDF and other sample results in the significant loss of DNA metabolizing effects. In this way, data potentially indicate that the goat UDF sample contains metabolite or similar organic compounds. Further, in vitro treatment of the goat, UDF sample shows clear anti-proliferative effects upon HCT-116 (up to 75%) and MCF-7 (up to 40%). Conclusion: This study signifies the clear differences in DNA metabolizing effects of goat UDF over other selected animal sources. Furthermore, the observed DNA metabolizing effects of goat UDF well correlate with anti-proliferative effects upon HCT-116 and MCF-7 cells. This study is a first report to show the comparison of urine metabolites among various animals. Interestingly, findings propose an indirect link that may support the possible reasons behind xeno-tumor heterogeneity in the form of rare occurrences of colorectal and mammary cancer in goat over other ruminants, non-ruminants and human.
Keywords: Microbiome